Queensland Consumers’ Awareness and Understanding of Clinical Genetics Services - Wallingford, Courtney K.; Cutler, Katrina; Istiko, Satrio Nindyo; Fowles, Lindsay F.; Lamb, Rachel; Bean, Jessica; Healy, Louise; Hondow, Gary; Pratt, Gregory; Vidgen, Miranda E.; Waddell, Nicola; Evans, Erin; et al. (Frontiers in Genetics, 2020)
As genetic testing becomes increasingly utilized in health care, consumer awareness and understanding is critical. Both are reported to be low in Australia, though there are limited studies to date. A consumer survey assessed perceived knowledge, awareness and attitudes toward genetic medicine, prior to consumers’ genomics forums in Queensland in 2018 and 2019. Data was analyzed using t-test and Mann-Whitney analysis to detect any associations between sociodemographic factors and familiarity or attitudes. This highly educated and experienced health consumer cohort reported they were significantly more familiar with the healthcare system generally than genetic medicine specifically (p<0.0001). Consumers perceived that genetic testing would be significantly more important in the future than it is currently (p<0.0001). Consumers agreed that genetic testing should be promoted (91.4%), made available (100%), better funded (94.2%), and offered to all pregnant women (81.6%). The preferred learning modality about genetics was internet sites (62.7%) followed by talks/presentations (30.8%). Benefits of genetic testing, reported in qualitative responses, included the potential for additional information to promote personal control and improve healthcare. Perceived concerns included ethical implications (including privacy and discrimination), and current limitations of science, knowledge and/or practice. This study demonstrates that even knowledgeable consumers have little familiarity with genetic medicine but are optimistic about its potential benefits. Ethical concerns, particularly concerns regarding genetic discrimination should inform legislation and policy and consumers are supportive of online resources in increasing genomic literacy.